Abrasion resistant glass-ceramic coatings reinforced with WC-nanoparticles - Copoglu, Nurullah; Cicek, Bugra (ELSEVIER SCIENCE SA, 2021)
The glass ceramic coatings reinforced with nano-WC hard ceramic particles used in the study were designed to remove stress points in the vitreous matrix. Coatings were applied to cast iron surfaces by the wet spraying method and fired at 770 degrees C for 12 min. The abrasion resistance of the samples was evaluated with a Taber abrasion device with H18 wheels and the changes in SEM, color, gloss, mass loss, and surface roughness values were analyzed before and after the abrasion test of the samples. The results showed that, the addition of 2.5 wt% nano-WC (W25) created the lowest mass loss and the lowest change in the surface properties. The lowest amount and the size in the pores were also observed in the W25 sample. It was observed that agglomeration occurred with the increase of nano-WC ratio in the samples and the abrasion resistance decreased.
Keywords: Glass-ceramics; Vitreous coating; Abrasion resistance; Nanoparticle; Agglomeration; Scheelite; PARTICLES; Materials Science; Physics